Dominating Energy of Operations on Intuitionistic Fuzzy Graphs - Kalimulla, A.; Vijayaragavan, R.; Sharief Basha, S. (International Journal of Engineering and Technology, 2018)
The concept of energy of an Intuitionistic Fuzzy Graph is extended to dominating Energy in operations on Intuitionistic Fuzzy Graph. In this paper, We have obtained the value of dominating Energy in different operations such as complement, Union, Join, Cartesian product and composition between two intuitionistic Fuzzy graphs. Also we study the relation between the dominating Energy in the operations on two Intuitionistic Fuzzy Graphs.Â Â